Multiple game trading strategy of multiple virtual power plants considering carbon trading - Chu, Tianfeng; An, Xingchen; Zhu, Yu; Wang, Xueying; Deng, Limin (Frontiers in Energy Research, 2023)
The large-scale access of distributed energy resources has a certain impact on the power grid, so distributed energy resources cannot participate in the power market transactions alone. The concept of the virtual power plant (VPP) has thus emerged, which can aggregate distributed power sources and controllable loads in a region for coordinated regulation. The trading of VPPs should not only consider the economy but also its degree of low carbon. Therefore, this paper constructs a unified bidding strategy for multi-VPPs that considers carbon–electricity integration trading. We design a multi-game trading strategy among multi-VPPs to achieve unified trading, after each VPP determines its internal trading strategy. Finally, through simulation, we verify that the multiple game strategy between multi-VPPs that considers carbon trading here proposed can effectively improve the efficiency and trading income of VPPs and promote the consumption of new energy.